DETERMINAN KEBIJAKAN DIVIDEN PADA PERUSAHAAN PERKEBUNAN TERDAFTAR DI BEI 2019-2023 - Martha, M. Tondi; Agrianti Komalasarii (E-journal Field of Economics, Business and Entrepreneurship (EFEBE), 2025)
Indonesia's plantation sector experienced significant fluctuations between 2019 and 2023, affecting corporate dividend policies. This study aims to analyze the influence of institutional ownership, leverage, profitability, and free cash flow on dividend policy among plantation companies listed on the Indonesia Stock Exchange during 2019–2023. Using purposive sampling, 19 companies were selected and analyzed through multiple linear regression. The results indicate that institutional ownership and free cash flow have no significant effect on dividend policy. Leverage has a negative impact, suggesting that increased debt reduces a company's ability to pay dividends. Profitability has a positive effect, indicating that more profitable companies tend to distribute higher dividends. This study contributes to a deeper understanding of dividend policy determinants in Indonesia's plantation industry.